The Influence of Signaling on the Disfluency Effect in Multimedia Learning - Lai, Tingming; Zhang, Jinkun (Frontiers in Psychology, 2021)
Do students learn better with texts that are slightly harder-to-read(i.e., disfluent)? Previous research has yielded conflicting findings. The present study identified the boundary condition that determines when disfluent texts benefit learning. We used eye-tracking to examine the joint influence of text legibility (fluent vs. disfluent) and signaling (signaling vs. non-signaling) on multimedia learning. The results revealed that both disfluent text and signaling led to better transfer test performance, and there was also an interaction between them. Specifically, the disfluent text led to better learning outcomes with or without signaling, however, in the fluent text condition, only signaling facilitated learning. Eye movement parameters indicated that signaling guided learners to pay more attention to important content in the learning materials. The current results suggest that signaling can enhance individuals’ perceived fluency or familiarity to the material and guide the attention during multimedia learning, and the positive impact of disfluency on multimedia learning seems to be more stable and ubiquitous. We discuss these under the framework, hoping to contribute to multimedia teaching.